Openness and productivity of the Swiss economy - Reto Foellmi; Angela Fuest; Philipp an de Meulen; Martin Micheli; Torsten Schmidt; Lina Zwick (Swiss Journal of Economics and Statistics, 2018)
This paper analyzes the connection between openness and economic performance in Switzerland. Considering different dimensions of openness, we show that the Swiss economy is classified as relatively open. Nevertheless, there still is potential to further increase international integration, particularly through deregulation in the services sector. We also show that for some branches in the Swiss manufacturing sector, increases in international trade are associated with higher productivity in the long run. With regard to financial openness, we show that in the aftermath of the financial crisis, Switzerland mainly suffered from capital retrenchment. Foreign capital inflows were of minor importance. Short-run costs due to high volatility of capital flows might therefore be lower than widely perceived.
Keywords: O40; F10; F30; 330; Productivity; Openness; Trade barriers